Aortic valve regurgitation and the congenitally bicuspid aortic valve: a clinico-pathological correlation. - Sadee, A S (1992)
OBJECTIVE--To investigate the morphology of congenitally bicuspid aortic valves causing pure valve regurgitation. DESIGN--A case series collected over five years. SETTING--An academic hospital. PATIENTS AND METHODS--One hundred and forty eight excised congenitally bicuspid aortic valves. The morphological findings were correlated with sex, age, clinical history, and data on haemodynamic function before operation. Pure valve regurgitation was defined as grade 3-4/4 with a gradient less than 30 mm Hg. Aortic root dilatation was evaluated angiographically or echocardiographically or both. RESULTS--Three types were recognised: valves that were purely bicuspid (23%), bicuspid valves with a raphe (34%), and valves with an additional indentation of the free edge of the conjoined cusp (43%). In 14 cases pure valve regurgitation was present. Dilatation of the aortic root was present in 47 cases. The relative risk for regurgitation when the aortic root was dilated (compared with no dilatation) was 3.99. The relative risk for valve regurgitation when there was indentation of the conjoined cusp (compared with no indentation) was 4.95. The mean age at operation in patients with pure regurgitation was 56 years, which is significantly younger (p = 0.0008) than that of patients with a congenitally bicuspid valve with combined valve stenosis and regurgitation (64.7 years). CONCLUSIONS--Congenitally bicuspid aortic valves with a central indentation of the free edge of the conjoined cusp seem particularly likely to develop pure aortic valve regurgitation.